Early Stimulation, Detection and Intervention for Growth and Development of Children (ESDIGDC) for Preschooler in Balowerti Health Center, Kediri - Eri Puji Kumalasari; Indasah Indasah; Byba Melda Suhita (Humanistic Network for Science and Technology (HNST), 2018)
Early Stimulation, Detection and Intervention for Growth and Development of Children (ESDIGDC) is an effort to monitor and collect and find early existence of irregularities and prevent the incidence of permanent disturbance through examination of growth, development and mental emotional condition of children. The objective of the study was to explore the implementation of ESDIGDC program in preschool children In Balowerti Health Center, Kediri. The study design used was qualitative research with phenomenology approach. Sampling technique in this research was purposive sampling with the sample size of 6 informants. Data were collected using indepth interview technique with semi-structured question. The result of the research shows that the implementation of ESDIGDC program influenced the development of ESDIGDC program in every year and will cause positive impact for both health worker and preschooler. The process of ESDIGDC program implementation was influenced by several factors. Based on the research, further research on the implementation of ESDIGDC program is needed. Keywords: ESDIGDC; preschooler; growth; development